You can read off the slope and \(\displaystyle y\) intercept in the first one, because it is already in \(\displaystyle y = mx + c\) form... \(\displaystyle m\) is the slope and \(\displaystyle c\) is the \(\displaystyle y\) intercept...

\(\displaystyle y = -2x + 8\).

To find the \(\displaystyle x\) intercept, let \(\displaystyle y = 0\) and solve for \(\displaystyle x\).

For the second

\(\displaystyle 3y + 2x = -12\)

\(\displaystyle 3y = -2x - 12\)

\(\displaystyle y = -\frac{2}{3}x - 4\).

Now you can do the same process as the first question.